Analisis Pengaruh Parameter Oseanografi Terhadap Nilai Produktivitas Primer Bersih Di Perairan Selat Makassar Dan Perairan Laut Arafura - Arjuno Yo Indarto; Dyah Ayu Sulistyorini (Jurnal Kelautan, 2026)
ABSTRACTThe The Makassar Strait and Arafura Sea are strategic waters because these waters are passed by the Indonesian Throughflow which not only carries water masses but also allows nutrient transport and primary productivity. Capture fisheries yields depend on the net Primary Productivity Value resulting from phytoplankton or chlorophyll-a activity in a body of water. Primary productivity value can be influenced by oceanographic parameters, nutrients, light, and Photosynthetically Available Radiation (PAR). The purpose of this study is to determine and analyze the differences in Primary Productivity Values in the waters of the Makassar Strait and Arafura Sea by utilizing Aqua-MODIS satellite imagery using the Vertically Generalized Production Model (VGPM) method in the 2022-2024 study period. The results showed that the Makassar Strait and Arafura Sea have different oceanographic characteristics, with oceanographic parameters having a major influence on Primary Productivity Values in the Makassar Strait and Arafura Sea. NPP variability is influenced by changes in oceanographic parameters and ENSO climate change, where in the Makassar Strait the highest NPP is obtained during La-Nina conditions while in the Arafura Sea the highest NPP conditions are obtained during Normal conditions.Keywords: Net Primary Productivity; Oceanographic Parameters; ENSO; Makassar Strait; Arafura SeaABSTRAKPerairan Selat Makassar dan Laut Arafura merupakan perairan yang strategis karena perairan ini dilewati oleh Arus Lintas Indonesia yang tidak hanya membawa massa air tetapi juga memungkinkan adanya transport nutrient dan produktivitas primer. Hasil perikanan tangkap bergantung dengan Nilai Produktivitas Primer bersih hasil dari aktivitas fitoplankton atau klorofil-a pada suatu perairan. Nilai Produktivitas Primer dapat dipengaruhi oleh parameter oseanografi, unsur hara, cahaya, dan Photosynthetically Available Radiation (PAR). Tujuan dari penelitian ini yaitu untuk mengetahui dan menganalisis perbedaan Nilai Produktivitas Primer pada perairan Selat Makassar dan Laut Arafura dengan memanfaatkan citra satelit Aqua-MODIS menggunakan metode Vertically Generalized Production Model (VGPM) pada rentang waktu kajian tahun 2022-2024. Hasil penelitian menunjukan antara Selat Makassar dan Laut Arafura memiliki karakteristik oseanografi yang berbeda, dengan parameter oseanografi memiliki pengaruh yang besar terhadap Nilai Produktivitas Primer di Selat Makassar maupun Laut Arafuara. Variabilitas NPP dipengaruhi oleh perubahan parameter oseanografi dan perubahan iklim ENSO, dimana pada Selat Makassar NPP tertinggi didapatkan pada saat kondisi La-Nina sedang pada Laut Arafura mendapatkan kondisi NPP tertinggi pada saat kondisi Normal.Kata kunci: Nilai Produktivitas Primer; Parameter Oseanografi; ENSO; Selat Makassar; Laut Arafura